2014
DOI: 10.1016/j.ijgo.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and acceptability of a mifepristone-misoprostol combined regimen for early induced abortion among women in Mexico City

Abstract: The combined mifepristone and buccal misoprostol regimen was found to be highly effective and acceptable among Mexican women. www.ClinicalTrials.gov: NCT00386282.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
(20 reference statements)
4
7
1
Order By: Relevance
“…The rates of success and ongoing pregnancy in the present study were comparable with those published elsewhere [1,4]. A study from Mexico City demonstrated an overall success rate of 97.3%, reporting that less than 1% of patients experienced ongoing pregnancy [12]. The only other published study retrieved during a search of the literature comparing medical abortion outcomes among patients choosing to start a progestin-only implant at the time of the induced abortion and those who did not, was small (n = 78, with 39 participants in each group), did not control for pregnancy gestation, and failed to detect any significant difference in outcomes between the groups [9].…”
Section: Discussionsupporting
confidence: 89%
“…The rates of success and ongoing pregnancy in the present study were comparable with those published elsewhere [1,4]. A study from Mexico City demonstrated an overall success rate of 97.3%, reporting that less than 1% of patients experienced ongoing pregnancy [12]. The only other published study retrieved during a search of the literature comparing medical abortion outcomes among patients choosing to start a progestin-only implant at the time of the induced abortion and those who did not, was small (n = 78, with 39 participants in each group), did not control for pregnancy gestation, and failed to detect any significant difference in outcomes between the groups [9].…”
Section: Discussionsupporting
confidence: 89%
“…13 The overall efficacy and continuing pregnancy rate after mifepristone followed by buccal misoprostol is 96.6% and 0.8%, respectively, through 70 days of gestation in the 33,846 women who were included in this systematic review (Table 1). However, only 332 women are reported in the literature between 64 and 70 days of gestation from three trials [14][15][16] with 304 of the patients from a single trial. 14 The overall efficacy at 64-70 days of gestation is 93.1%.…”
Section: Resultsmentioning
confidence: 99%
“…14,22,23 Outcomes by gestational age were reported for 12,050, 4,032, and 2,153 women with pregnancies 49 days or less, 50-56 days, and 57-63 days of gestation, respectively. All studies used 800 micrograms misoprostol buccally 11,[14][15][16][22][23][24][25][26][27][28][29][30] except for one study that reported clinical outcomes with 400 micrograms misoprostol buccally. 31 One study described the actual time interval at which patients administered misoprostol after mifepristone, reporting a median interval of 48 hours (range 25-52 hours) for women who took mifepristone at home and a median interval of 47 hours (range 26-54 hours) for women that took mifepristone in the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…By 2013, 69% of legal abortions in Mexico City were medical abortions [15,16]. Experience in the outpatient use of medicines has been documented for pregnancies up to a gestational age of 63 days (9 weeks), administering 200 mg mifepristone orally followed by 800 μg misoprostol orally, with a success rate of 97.3% [16].…”
Section: Discussionmentioning
confidence: 99%